The dominant factors associated with stunting among two years children in five provinces in Indonesia - Ramadhani Fitri; Ali Khomsan; Cesilia Meti Dwiriani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting is a significant malnourishment problem in Indonesia. The 2021 Indonesian Nutritional Status Study (SSGI) reported that there are five provinces with a high prevalence of stunting (>30%). Age under two years (old age) is the golden period during which children overgrow, and malnutrition during this period can still be corrected. This study analyzed the dominant factors associated with stunting in two-year-old children from five provinces: Aceh, NTB, NTT, West Sulawesi, and Southeast Sulawesi. This cross-sectional study used secondary data from the SSGI 2021. The subjects were 4,554. Children (0-23 months) under five. The 2021 SSGI study was conducted in 34 provinces and 514 regencies/cities from January to December 2021. Data were collected through interviews using the SSGI 2021 questionnaire and anthropometric measurements. Statistical applications were used for data processing. Data analysis was performed using multiple logistic regression tests with the criteria of p<0,05 and a confidence interval (CI) of 95%. The risk factors associated with stunting in children from the five provinces were underweight (OR=9,367), age 6-11 months (OR=1,386), age 12-23 months (OR=1,386), diagnosis of measles (2,5681 CI), male sex (OR=1,400), family size ≥ 8 people (OR=1,612), poor sanitation (OR=1,273 CI 95% 1,041-1,556), and the father's occupation as a farmer/occupation/fisherman/driver (OR=1,278). In conclusion, being underweight is the dominant factor associated with stunting in toddlers.